Faktor – Faktor yang Mempengaruhi Purchase Intention Produk Private Label Sirup Indomaret di Jakarta - Edwin Rommel Yudistira (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
Indonesia's retail business has grown with the increasing number of existing retailers. The presence of this retailer gave rise to private label products in Indonesia. Private labels are one of the retailer's strategies to be competitive in the market. The purpose of this research is to analyze the influence of: Perceived Quality, Perceived Risk, Perceived Value, Perceived Price, Advertisement, Packing, Store Image, Social Influence, Consumers' Attitude to Purchase Intention Indomaret private label products in Jakarta. Data were obtained by distributing questionnaires to 350 respondents who met the criteria. Then the data were analyzed by classical assumption test, F test, t test, and analysis of the coefficient of determination. These results indicate that the Variable Perceived Quality, Perceived Risk, Perceived Value, Perceived Price, Advertisement, Packing, Store Image, Influence and Consumers' Attitude have a significant influence on Purchase Intention. Whereas Social Influence does not have a significant influence on Purchase Intention. Suggestion for research is that further research can be conducted with larger samples and different and more specific independent variables.